An economic analysis of policies for promoting economically efficient water heater systems operating under seasonal climatic conditions. Issue 2 (March 2016) - Yurtsev, Arif; Jenkins, Glenn P
This article reports on an economic cost-effective analysis of water heating systems including solar water heating systems. This study finds that in situations where there is a winter, or a rainy season, the choice of the source of energy for the solar water heating systems' back-up during this period is critical for its overall cost-effectiveness. It is found that in the conditions of North Cyprus, an solar water heating systems with electricity back-up is far superior to using electricity alone; however, it is inferior to heating water with either a liquefied petroleum gas water heater alone or an solar water heating systems with an liquefied petroleum gas back-up. Policies to promote water heating systems that reduce the use of electricity should not encourage the installation of solar water heating systems with electricity back-up. An liquefied petroleum gas water heater or an solar water heating systems with an liquefied petroleum gas back-up are economically more cost-effective, with or without the inclusion of the social cost of carbon estimates.